Does the cause related market really predict the consumer purchase intention? - Naqvi, Muhammad Hasnain Abbas; Naqvi, Mishal; Bokhari, Ijaz (UW Journal of Management Sciences, 2023)
Purpose: The current study intents to evaluate how to cause promotion strategy shapes customer viewpoint, perception, and purchasing behavior. To achieve the research objectives of the present study considered the integrated model based on the theory of planned behavior. The integrated model evaluates the role of causal marketing towards the consumer purchase intention. In addition to that the present study proposed that the consumer perception and attitude, and brand loyalty significantly mediate the association between causal marketing and consumer purchase intention. Design and Methodology: The present study used the non-probability sampling technique. The association among the latent constructs was evaluated using the structural equation modeling technique. The findings of the current study revealed a link between causal marketing and purchasing behavior and attitude. Consumers are more inclined to support corporations that participate in cause campaigns and acquire a favorable view of the firm and its products. The study's main result is that while consumers may be more favorable to causal Marketing, the trademark must be regarded to have a usual link with the cause. Furthermore, causal marketing has the potential to elicit a more favorable shift in brand attitude than sales promotion. This shift in attitude is influenced by the consumer's perception of the approach itself. Findings: Finding of present study affirms that brand loyalty and consumer perception, and attitude significantly and positively linked with the consumer purchase intentions. Furthermore, the findings affirm that brand loyalty and consumer perception, and attitude significantly and positively mediate the association between the causal marketing and consumer purchase intention. Implications: Causal Marketing may also elicit a favorable shift in brand attitude more successfully than a promotional strategy. This shift in mindset is dependent on the consumer's reaction to the approach itself. Keywords: Causal Marketing, Brand Loyalty, Consumer perception and attitude, Consumer purchase intention.